Analysis of Temporal and Spatial Evolution Characteristics of Rainfall in Dongguan in the Past 30 Years - WANG Qiuliang; SUN Xiang; GAN Dufen; MEI Xinpei; CHENG Jie; ZAN Xiongfeng (Renmin Zhujiang)
Dongguan is an important city in the Guangdong-Hong Kong-Macao Greater Bay Area,which is a major contributor to the economic development of this area.However,its urban planning,rational allocation of water resources,flood prevention and disaster reduction are severely affected by torrential rain and floods,and thus its high-quality economic development is seriously hindered.Therefore,by using the 32-year daily rainfall data of 30 hydrological stations in Dongguan,this paper adopts methods such as GIS,the Mann-Kendall test,moving average,and cumulative anomaly to discuss the temporal and spatial distribution of rainfall in Dongguan.The results reveal that in the past 32 years,the temporal and spatial distribution of annual rainfall has gradually increased from west to east with a significant rising trend over time.During the flood season,the rainfall increases sequentially from west to east and gradually decreases from the central part to west,and from the central part to east,it drops before it rises.Rainfall in the flood season accounts for about 60%~95% of the annual total.The rainfall in the non-flood season is prominent in the central part,with great differences between east and west,namely that the rainfall in the central part tends to decrease gradually to both sides,and the southwestern part registers the smallest.The center of the maximum rainfall in the four seasons moves from the central part to the northeast,east,and central,and the southwest still records the minimum rainfall.The monthly average rainfall generally shows an increasing trend from west to east:Many years of data indicates that the average rainfall in June is the largest,accounting for 18.58% of the rainfall all year,while December sees the smallest,accounting for 1.88% of the yearly total.The research results can provide reference and support for the later development of Dongguan.